Role of the monomeric GTPase Rho in hematopoietic progenitor cell migration and transplantation - Göttig, Stephan; Möbest, Dietrich; Rüster, Brigitte; Grace, Bithiah; Winter, Sylvia; Seifried, Erhard; Gilles, Jens; Wieland, Thomas; Henschler, Reinhard (European journal of immunology, 2006)
To investigate the role of the monomeric guanosine triphosphatase (GTPase) Rho on migration of hematopoietic progenitor cells (HPC), we employed different clostridial toxins which inhibit the Rho family of GTPases. Pretreatment with C2I-C3, a cell-accessible C3 transferase fusion protein that targets Rho, increased chemokinetic migration of the factor-dependent multipotent cell line Factor Dependent Cell Paterson with mixed lineage differentiation potential (FDCP-mix) and of primary lineage marker-depleted HPC in vitro. In contrast, treatment with lethal toxin (LT) from Clostridium sordellii, which predominantly inactivates Rac, and with toxin B from C. difficile, which inactivates Rho, Rac and Cdc42, decreased in vitro migration. When HPC pretreated with LT or toxin B were transplanted into mice, homing to the bone marrow was impaired, whereas C2I-C3 treatment did not alter HPC homing. However, in a competitive hematopoietic repopulation experiment in C57BL/6 mice, pretreatment of bone marrow cells with any of the inhibitors, including the Rho inhibitor C2I-C3, resulted in suppressed donor-type hematopoiesis. Our data indicate that whereas Rac supports HPC cell cycling, migration, short-term homing and hematopoietic regeneration, Rho coordinates down-regulation of HPC migration and is required for hematopoietic regeneration.
First published: 27 December 2005
Gesehen am 31.03.2022